Forecasting patronage factors of Islamic credit card as a new e-commerce banking service: an integration of TAM with perceived religiosity and trust - Jamshidi, D. (Emerald Group Publishing Ltd., 2016)
Purpose: Understanding the important patronage factors of Islamic credit card as a new e-commerce banking service is essential for bankers and users. Although some previous studies have focused on the factors that influence adoption of Islamic credit card, there are few empirical research studies that use a well-established adoption model that helps bankers and consumers to accept and use the Islamic credit card. This study aims to provide such a model to facilitate the adoption of Islamic credit card. Design/methodology/approach: In response, a conceptual model was developed that combines the Technology Acceptance Model (TAM) with perceived religiosity (a new developed construct in this study) and trust to explain usage intention of this new banking product. Accordingly, the data were collected from 327 bank customers, and the results supported the applicability of TAM to describe usage behavior of Islamic credit card. Besides, the newly developed construct (perceived religiosity) increased the TAM power regarding explaining adoption of a new e-commerce banking service. Findings: Theoretically, the results of this study advocate that perceived religiosity increase the TAM predictive power to clarify intention to use. While, perceived usefulness, perceived ease of use and attitude explained low level of the variance regarding intention to use, by adding perceived religiosity to TAM, these constructs contributed to an increase in the described variance, therefore offering a better explanatory power. In addition, the proposed joint TAM, perceived religiosity and trust explained 57.1 per cent of usage behavior variance. These results are of prime importance, as, to the best of the authors’ knowledge, this is the first study that proves the applicability of TAM for explaining adoption and usage of the Islamic credit card. Originality/value: The findings of the current study showed that perceived usefulness is an important factor effecting people’s intention to use the Islamic credit card. Consequently, managers need to first ensure that the Islamic credit card and its services are technically sound and work in an appropriate manner. The focus should be on promoting speed, efficiency and effectiveness of this new product. In financial part, there is a need to reduce the interest rate in the long run to encourage potential users to consider the usage of the Islamic credit card and its offered services.